FEATURES OF PSYCHOLOGICAL WORK WITH EMOTIONAL STATES OF PARENTS OF YOUNG CHILDREN WITH PSYCHO-PHYSICAL DISORDERS - Shulzhenko, Dina (PSYCHOLOGICAL JOURNAL, 2017)
The most common in correctional education is a child anomalies classification by type of violation. Such knowledge defined the content and methods of work with the child and form of education and training. The scholarly objective is to study: problems related to the illness of the child which determine the emotional state of parents having a child with special needs; the stages of experience of the birth of a sick child, and types of emotional reactions of parents. Traditionally the problem of families who raise children with special needs are considered exclusively through the prism of the child’s problems. In most cases, assistance is limited to consulting on the issues of upbringing and education, however little attention is given to a very serious aspect, i.e. the emotional state of the parents themselves. To help them, it is important to understand what happens to a person when his/her child is diagnosed with a disease and how it affects the life on the whole. The article analyzes the scholarly data and approaches to the study of: problems of parents arising from their child’s illness; emotional states in parents raising a child with developmental impairments; and stages of experience of having a sick child. One of the main prerequisites for the adequate development of a child is upbringing in an emotionally favorable and stable social environment. The family is one of these environments; this is where the foundation are laid for future skills required for successful human existence in the outside world. The practical objective of our research is the basis for designing psychological support for parents raising a child with developmental disabilities.